2016
DOI: 10.1002/ejlt.201600209
|View full text |Cite
|
Sign up to set email alerts
|

Composition and oxidative stability of oil from Salvia hispanica L. seeds in relation to extraction method

Abstract: This study evaluated the influence of the extraction method on the composition, quality and oxidation stability of chia seed oil. Commercial chia seeds were purchased from a local market and oils were obtained using various methods: Classical Soxhlet extraction using hexane and acetone, supercritical fluid extraction with CO2 at 70 and 90°C, and screw‐pressing from native seeds (cold process), and from seeds conditioned at 110°C (hot process). The oils were characterized by their contents of sterols, tocochrom… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
39
5
5

Year Published

2018
2018
2023
2023

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 53 publications
(55 citation statements)
references
References 25 publications
6
39
5
5
Order By: Relevance
“…2b) were very similar (PUFA and ALA concentrations around (81% and 59%, respectively). Our results agree well with those of other authors, who used chia seeds from several geographical origins, and applied different extraction methods and operational conditions [7][8][9][10][11][17][18][19][20].…”
Section: Supercritical Co 2 Extractionsupporting
confidence: 92%
See 1 more Smart Citation
“…2b) were very similar (PUFA and ALA concentrations around (81% and 59%, respectively). Our results agree well with those of other authors, who used chia seeds from several geographical origins, and applied different extraction methods and operational conditions [7][8][9][10][11][17][18][19][20].…”
Section: Supercritical Co 2 Extractionsupporting
confidence: 92%
“…Thus far, different solvents (ethyl acetate, acetone, propane, petroleum ether and hexane) and extraction techniques (cold and hot pressing, Soxhlet, Ultrasound-Assisted Extraction and Pressurized Liquid Extraction) have been applied to obtain chia seed oil [7][8][9][10][11]. A viable and eco-friendly alternative to the use of organic toxic solvents is the extraction with supercritical CO 2 (scCO 2 ), which is non-toxic, non-flammable, non-mutagenic and carcinogenic and is abundant and inexpensive.…”
Section: Introductionmentioning
confidence: 99%
“…The CP technology has been considered as an ideal edibleoil-producing method, because it can produce high-quality products without high temperature or chemical treatment. As reported in previous studies, compared with the HP methods, the chia seed oil derived from the CP technology contained significantly higher tocopherols and squalene (Dąbrowski, Konopka, Czaplicki, & Tańska, 2017;Duthie, Crozier, & Goldberg, 2003), which might imply that the consumption of the cold-pressed oils was good for human's health. However, several studies claimed that the polyphenol compounds (PC), and some other minor components, such as total tocopherols (TTCs), in hot-pressed oil were higher than Investigation on lipid metabolism by Sprague-Dawley rat model .…”
Section: Introductionmentioning
confidence: 56%
“…CPO contained higher TTC and PC than HPO and EAO ( P < 0.05), which suggested that cold process technology might protect this kind of bioacitive component. A recent study showed that compared with hot press methods, cold press technology could preserve squalene in Salvia hispanica L. seed oil (Dąbrowski et al., ). Moreover, Nakić et al.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation